1978
DOI: 10.4319/lo.1978.23.1.0053
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved silica in pore waters of Lakes Ontario, Erie, and Superior sediments

Abstract: The distribution of dissolved silica in pore waters from Lakes Ontario, Erie, and Superior sediments is not directly related to the deposition of diatomites from the overlying water. It is proposed that silica concentrations in the pore waters are controlled by dissolution of fcrroaluminum silicate, AI,,Fe,,"+(SiO,),(OH)~~,-~~. The cryptocrystalline complex is formed in the sediments by the reaction of biogenic silica with aluminum and ferric oxyhydroxides or by the hydrolysis of clay minerals. A massive episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 23 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…The concentrations of DSi in the interstitial water of the top part of the sediment profile in Lake Kuutsjärvi (21-24 mg l -1 , Fig. 4) were high compared to these values and to other values measured from the uppermost layers of lake sediment profiles (Harriss 1967;Bailey-Watts 1976;Nriagu 1978;Cornwell and Banahan 1992;Parker et al 1977;Peinerud 2000), where values above 20 mg l -1 were mostly found only at 10-20 cm sediment depth. As supersaturation of the sediment interstitial water with DSi is a factor retarding further dissolution (cf.…”
Section: Autochthonous Diatom Production?mentioning
confidence: 59%
“…The concentrations of DSi in the interstitial water of the top part of the sediment profile in Lake Kuutsjärvi (21-24 mg l -1 , Fig. 4) were high compared to these values and to other values measured from the uppermost layers of lake sediment profiles (Harriss 1967;Bailey-Watts 1976;Nriagu 1978;Cornwell and Banahan 1992;Parker et al 1977;Peinerud 2000), where values above 20 mg l -1 were mostly found only at 10-20 cm sediment depth. As supersaturation of the sediment interstitial water with DSi is a factor retarding further dissolution (cf.…”
Section: Autochthonous Diatom Production?mentioning
confidence: 59%
“…Silica concentrations often increase with depth in lakes, usually because of dissolution phenomena affecting sedimenting diatom frustules (e.g. Nriagu, 1978). The presence of large diatom species with well-silicified valves in the deep zone of Lake Tovel has also been observed elsewhere (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As the diatoms died and were removed from the water column or surface sediments, the silica was recycled, leading to few remains in the sediment. Extensive dissolution and silica recycling has been observed in more productive temperate systems (e.g., Parker et al 1977aParker et al , 1977bNriagu 1978;Conley et al 1988;Ryves et al 2013) and in Alaska (Cornwall and Banahan 1992). The increased terrestrial vegetation production, along with the continual presence of permafrost, may have reduced input of silica to the lake.…”
Section: Diatom-free Zones In Arctic Lake Sedimentsmentioning
confidence: 99%